Compound fractures - White, Stephen, 1951- (Dutton, 2013)
Boulder psychologist Alan Gregory must solve a deadly mystery in Eldorado Springs that has been brewing for more than a decade and revisit the cruel ethical dilemma that turned his life upside down as a young psychologist.